Teknoekonomi Penyingkiran Senyawa Sulfur dari Kondensat Gas Alam dengan Metode Desulfurisasi Oksidatif-Ekstraktif - Tri Partono Adhi; Sardenianto Sardenianto; Antonius Indarto (Jurnal Rekayasa Proses, 2022)
In the oil and gas production process, apart from hydrocarbons, a number of impurities are produced, including CO2 and sulfur in various concentrations, depending on the conditions and characteristics of the reservoir and the location where the oil and gas is located. To process sulfur removal from condensate, the common technology is HDS (Hydrodesulfurization). However, with process requirements such as high temperature, pressure, and intensive hydrogen consumption, an alternative technology is needed for this desulfurization. One of them is oxidative-extractive desulfurization. Technical and economic evaluations to determine the feasibility of applying on an industrial scale need to be studied further. The study of oxidative-extractive desulfurization process of sulfur compounds (represented as dibenzothiophene, DBT) was carried out using H2O2/formic acid as oxidizing agent and catalyst, as well as extraction with DMF. For a capacity of 1000 bpd of condensate with 1%-wt sulfur, desulfurization was successfully carried out with sulfur removal of 96.55% and condensate recovery of 99.41%. A processing fee of 9.14 USD/barrel is required, of which 84% is required for chemicals. The alternative process configuration for DMF recovery succeeded in reducing chemical costs by 35.5% and reducing total processing costs by 27.0% to 6.67 USD/barrel. In this alternative process configuration, 95.80% sulfur removal was achieved with condensate recovery of 99.21%.